A Hundred Years of Texas Waterfowl Hunting : The Decoys, Guides, Clubs, and Places, 1870s to 1970s - Sawyer, R. K. (Robert Knowlton), 1956- (Book collections on Project MUSE., 2012)
The days are gone when seemingly limitless numbers of canvasbacks, mallards, and Canada geese filled the skies above the Texas coast. Gone too are the days when, in a single morning, hunters often harvested ducks, shorebirds, and other waterfowl by the hundreds. The hundred-year period from the mid-nineteenth to the mid-twentieth centuries brought momentous changes in attitudes and game laws: changes initially prompted by sportsmen who witnessed the disappearance of both the birds and their spectacular habitat. These changes forever affected the state's storied hunting culture. Yet, as R.K. Sawyer discovered, the rich lore and reminiscences of the era's hunters and guides who plied the marshy haunts from Beaumont to Brownsville, though fading, remain a colorful and essential part of the Texas outdoor heritage. Gleaned from interviews with sportsmen and guides of decades past as well as meticulous research in news archives, Sawyer's vivid documentation of Texas' deep-rooted waterfowl hunting tradition is accompanied by a superb collection of historical and modern photographs. He showcases the hunting clubs, the decoys, the duck and goose calls, the equipment, and the unique hunting practices of the period. By preserving this account of a way of life and a coastal environment that have both mostly vanished, A Hundred Years of Texas Waterfowl Hunting also pays tribute to the efforts of all those who fought to ensure that Texas' waterfowl legacy would endure. This book will aid their efforts, along with those of coastal residents, birders, wildlife biologists, conservationists, and all who are interested in the state's natural history and in championing the preservation of waterfowl and wetland resources for the benefit of future generations. For more information, visit the author's website at www.robertksawyer.com.